Operationalizing culturally relevant leadership learning - Beatty, Cameron C.; Guthrie, Kathy L. (Contemporary perspectives on leadership learning., 2021)
"This book is a practical resource designed to raise leadership educators understanding of culturally relevant leadership pedagogy for the purpose of creating inclusive learning spaces that are socially just for students. For leadership educators seeking personal and professional development to assist in building and enhancing their levels of cultural competence in leadership education, this book is a guide. The audience for the book ranges from new and entry-level leadership educator roles to senior scholars in leadership education. Operationalizing Culturally Relevant Leadership Learning, provides leadership educators with a substantive and comprehensive approach to the topic, offering personal narratives from leadership educators who have operationalized the model in their own personal and professional contexts. We believe that reframing leadership education with the culturally relevant leadership learning model, leadership educators will be able to integrate new insights into their own pedagogy and practice and move towards action. This book illustrates how leadership educators can shift the way they experience and facilitate leadership learning. By framing the operationalization of culturally relevant leadership learning, this book discusses the why, who, what, where, when, and how of developing culturally relevant and socially just leadership education. Readers of this text are encouraged to actively engage in the content through the questions each chapter pose and consider for themselves how culturally relevant leadership learning can be implemented in their own context"--